Role Allocation and Scheme in Software Engineering Course Projects - Alipour, Ghafour (Electronic Communications of the EASST, 2011)
Role is a set of behavioural actions and responsibilities one takes in a specific situation. We play different roles with our family, at work as well as in other environments. Differences among the role definitions reach mainly from the different emphasis of the software development method itself. Agile software development methods define roles to enhance communication and to produce a better product. In this paper, we describe a role allocation and scheme method whose data were gathered in student’s projects in software engineering course in the university.